Safety and efficacy of the additive consisting of muramidase produced by Trichoderma reesei DSM 32338 (Balancius™) for use in weaned piglets (DSM Nutritional products Ltd) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Fašmon Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2021)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of muramidase produced by Trichoderma reesei DSM 32338 (Balancius™) as a feed additive for weaned piglets. The additive has been previously assessed by the FEEDAP Panel in the context of other applications, and in the current assessment the applicant requests for an extension of use. Based on the data available in a sub‐chronic oral toxicity study, the Panel concluded that the additive is safe for weaned piglets at the maximum recommended level of 65,000 LSU(F)/kg feed. The additive is safe for the consumers and the environment but should be considered a potential respiratory sensitiser. The Panel could not conclude on the potential of the additive for skin/eye irritancy and skin sensitisation. The additive has the potential to be efficacious as a zootechnical additive for weaned piglets at the dose of 50,000 LSU(F)/kg feed.